Exosomes Mediated Transfer of Circ_0000337 Contributes to Cisplatin (CDDP) Resistance of Esophageal Cancer by Regulating JAK2 via miR-377-3p - Zang, Rukun; Qiu, Xiaowen; Song, Yipeng; Wang, Yang (Frontiers in Cell and Developmental Biology, 2021)
Background: Chemoresistance remains a major obstacle to the treatment of esophageal cancer patients. Exosome-mediated transfer of circular RNAs (circRNAs) has been reported to be related to the drug resistance in esophageal cancer. This study is designed to explore the role and mechanism of exosomal circ_0000337 on CDDP resistance of in esophageal cancer. Methods: Cell viability, proliferation, colony number, apoptosis, migration, and invasion were assessed by Cell Counting Kit-8 (CCK-8), colony formation, flow cytometry, and transwell assays. Circ_0000337, microRNA-377 (miR-377), and Janus kinase 2 (JAK2) level were detected by real-time quantitative polymerase chain reaction (RT-qPCR). Exosomes were isolated and detected by differential centrifugation and a transmission electron microscope. Protein levels of CD9, CD63, and JAK2 were tested by western blot assay. The binding relationship between miR-377 and circ_0000337 or JAK2 was predicted by circinteractome or Starbase, and then verified by dual-luciferase reporter assay. The biological role of exosomal circ_0032821 and CDDP on esophageal cancer cell growth was examined by xenograft tumor model in vivo. Results: Circ_0000337 and JAK2 were highly expressed, and miR-377 was decreased in CDDP-resistant esophageal cancer tissues and cells. Moreover, circ_0000337-containing exosomes secreted by CDDP-resistant esophageal cancer cells could promote CDDP resistance, cell growth, metastasis in CDDP-sensitive esophageal cancer cells in vitro. The mechanical analysis discovered that circ_0000337 functioned as a sponge of miR-377 to regulate JAK2 expression. Exosomal circ_0000337 increased the drug resistance of esophageal cancer in vivo. Conclusion: Exosomal circ_0000337 accelerated CDDP resistance of esophageal cancer cells partly by regulating the miR-377/JAK2 axis, hinting a promising therapeutic target for the esophageal cancer treatment.